Third year at malory towers - Blyton, Enid (Egmont London, 2006)
Third in the series. Two new girls have arrived at Malory Towers - and they couldn't be more different. Tomboy Bill spends more time with her horse than in the classroom, whilst American girl, Zerelda, seems determined not to fit in with the others